Enhancing TB case detection: experience in offering upfront Xpert MTB/RIF testing to pediatric presumptive TB and DR TB cases for early rapid diagnosis of drug sensitive and drug resistant TB. - Neeraj Raizada; Kuldeep Singh Sachdeva; Sreenivas Achuthan Nair; Shubhangi Kulsange; Radhey Shayam Gupta; Rahul Thakur; Malik Parmar; Christen Gray; Ranjani Ramachandran; Bhavin Vadera; Shobha Ekka; Shikha Dhawan; et al. (PLoS ONE)
Background Diagnosis of pulmonary tuberculosis (PTB) in children is challenging due to difficulties in obtaining good quality sputum specimens as well as the paucibacillary nature of disease. Globally a large proportion of pediatric tuberculosis (TB) cases are diagnosed based only on clinical findings. Xpert MTB/RIF, a highly sensitive and specific rapid tool, offers a promising solution in addressing these challenges. This study presents the results from pediatric groups taking part in a large demonstration study wherein Xpert MTB/RIF testing replaced smear microscopy for all presumptive PTB cases in public health facilities across India. Methods The study covered a population of 8.8 million across 18 programmatic sub-district level tuberculosis units (TU), with one Xpert MTB/RIF platform established at each study TU. Pediatric presumptive PTB cases (both TB and Drug Resistant TB (DR-TB)) accessing any public health facilities in study area were prospectively enrolled and tested on Xpert MTB/RIF following a standardized diagnostic algorithm. Results 4,600 pediatric presumptive pulmonary TB cases were enrolled. 590 (12.8%, CI 11.8-13.8) pediatric PTB were diagnosed. Overall 10.4% (CI 9.5-11.2) of presumptive PTB cases had positive results by Xpert MTB/RIF, compared with 4.8% (CI 4.2-5.4) who had smear-positive results. Upfront Xpert MTB/RIF testing of presumptive PTB and presumptive DR-TB cases resulted in diagnosis of 79 and 12 rifampicin resistance cases, respectively. Positive predictive value (PPV) for rifampicin resistance detection was high (98%, CI 90.1-99.9), with no statistically significant variation with respect to past history of treatment. Conclusion Upfront access to Xpert MTB/RIF testing in pediatric presumptive PTB cases was associated with a two-fold increase in bacteriologically-confirmed PTB, and increased detection of rifampicin-resistant TB cases under routine operational conditions across India. These results suggest that routine Xpert MTB/RIF testing is a promising solution to present-day challenges in the diagnosis of PTB in pediatric patients.